The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1177/0748233718778397
|View full text |Cite
|
Sign up to set email alerts
|

Mancozeb induces testicular dysfunction through oxidative stress and apoptosis: Protective role of N-acetylcysteine antioxidant

Abstract: Mancozeb (MZB) is one of the fungicides used in pest control programs that might affect human health including reproductive system. The aim of this study was to demonstrate the mechanisms through which MZB induces testicular tissue damage and the probable protective effect of N-acetylcysteine (NAC), a modified amino acid, with antioxidant property, against MZB toxicity in an animal model. Male albino mice ( n = 8) were exposed to different doses of MZB (250 and 500 mg/kg/day) by oral gavage without or with NAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 61 publications
(84 reference statements)
1
18
0
Order By: Relevance
“…On the other hand, serum total lipid content was significantly increased in female and male albino rats after being fed on diets containing chlorpyrifos (at 200 ppm), or chlorpyrifosmethyl (at 2000 ppm) for 12 weeks followed by a 3week recovery period (El-Tawil, 2014). It was also found that MNZ increased lipid peroxidation and protein carbonyl (Mohammadi et al, 2018). The increased cholesterol and LDL cholesterol levels could be attributed to hypothyroxinemia and inhibition of thyroid peroxidase that was induced by MNZ exposure as stated by Axelstad et al (2011).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…On the other hand, serum total lipid content was significantly increased in female and male albino rats after being fed on diets containing chlorpyrifos (at 200 ppm), or chlorpyrifosmethyl (at 2000 ppm) for 12 weeks followed by a 3week recovery period (El-Tawil, 2014). It was also found that MNZ increased lipid peroxidation and protein carbonyl (Mohammadi et al, 2018). The increased cholesterol and LDL cholesterol levels could be attributed to hypothyroxinemia and inhibition of thyroid peroxidase that was induced by MNZ exposure as stated by Axelstad et al (2011).…”
Section: Discussionmentioning
confidence: 84%
“…On the other hand, serum total lipid content was significantly increased in female and male albino rats after being fed on diets containing chlorpyrifos (at 200 ppm), or chlorpyrifos-methyl (at 2000 ppm) for 12 weeks followed by a 3-week recovery period (El-Tawil, 2014). It was also found that MNZ increased lipid peroxidation and protein carbonyl (Mohammadi et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Blood-testis barrier (BTB) was evaluated by the Evans blue extravasation method. 79,80 Evans blue (2% in saline, 3 mL/kg; Sigma-Aldrich) was given iv at 3 h before sacrificing followed by transcardial perfusion of NaCl 0.9% to remove the intravascular dye from the vessels until the drainage was colorless. Afterward, one testis was removed, weighed, dried in a desiccator oven for 48 h at 60 C, and reweighed.…”
Section: Assessment Of Oxidative Stress Parametersmentioning
confidence: 99%
“…Sperm parameters including motility, viability, and the number of sperms have been decreased by MZB (500 mg/kg) (Girish and Reddy, 2017). Another study in 2018 (Mohammadi-Sardoo et al, 2018) showed deleterious changes in the architecture of testis, oxidative stress imbalance, and apoptosis following MZB administration. It was also found to impair male fertility in rabbits with anti-spermatogenic and antisteroidogenic adverse effects (Elsharkawy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced production of ROS is caused by infections, varicocele, cigarette smoking, ionizing radiation, psychological stress, spinal cord injury, and environmental pollution like pesticides (Bui et al, 2018). Reactive oxygen species generation, as second messenger, and induction of oxidative stress is a potential mechanism involved in reprotoxicity of MZB (Girish and Reddy, 2017;Liu et al, 2017;Mohammadi-Sardoo et al, 2018), which leads to the induction of cell death and infertility.…”
Section: Introductionmentioning
confidence: 99%